Kemampuan Santri dalam Membaca Al-Qur’an Ditinjau Dari Profesioanlisme Guru (Qori’) (Analisis Metode Qiraati di API ASRI Tegalrejo Magelang) - Akhmad Ibnu Idris; Saebani Saebani (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2020)
Reading the Qur'an is something that must be mastered by the students in the Islamic Boarding School. The role of a teacher and the methods used become important in the learning cycle in an educational institution especially Islamic boarding school. Qiraati is one of the methods used in learning to read the Qur'an. One indicator that is the key to the success of students is able to read the Qur'an properly and correctly, namely the existence of a professional qori. This type of research is a descriptive study using a quantitative approach. The number of samples in this study were 89 students. The data analysis technique in this study uses simple linear regression analysis with the help of SPSS 24 application. The results of this study indicate that the influence of the qori 'professionalism variable on the ability of students to read the Qur'an has a significance value level of less than 0.05 (p <0 , 05). This shows that the qori professionalism variable 'affects the ability of students to read the Qur'an in the ASRI Islamic Boarding School Tegalrejo Magelang.